Engaging community members in setting priorities for nutrition interventions in rural northern Ghana - Maxwell Ayindenaba Dalaba; Engelbert A. Nonterah; Samuel T. Chatio; James K. Adoctor; Edith Dambayi; Esmond W. Nonterah; Stephen Azalia; Doreen Ayi-Bisah; Agnes Erzse; Daniella Watson; Polly Hardy-Johnson; Sarah H. Kehoe; et al. (Public Library of Science (PLoS), 2022)
This study used "Choosing All Together" (CHAT), a deliberative engagement tool to prioritise nutrition interventions and to understand reasons for intervention choices of a rural community in northern Ghana. The study took an exploratory cross-sectional design and used a mixed method approach to collect data between December 2020 and February 2021. Eleven nutrition interventions were identified through policy reviews, interaction with different stakeholders and focus group discussions with community members. These interventions were costed for a modified CHAT tool-a board-like game with interventions represented by colour coded pies and the cost of the interventions represented by sticker holes. Supported by trained facilitators, six community groups used the tool to prioritise interventions. Discussions were audio-recoded, transcribed and thematically analysed. The participants prioritised both nutrition-sensitive and nutrition-specific interventions, reflecting the extent of poverty in the study districts and the direct and immediate benefits derived from nutrition-specific interventions. The prioritised interventions involved livelihood empowerment, because they would create an enabling environment for all-year-round agricultural output, leading to improved food security and income for farmers. Another nutrition-sensitive, education-related priority intervention was male involvement in food and nutrition practices; as heads of household and main decision makers, men were believed to be in a position to optimise maternal and child nutrition. The prioritised nutrition-specific intervention was micronutrient supplementation. Despite low literacy, participants were able to use CHAT materials and work collectively to prioritize interventions. In conclusion, it is feasible to modify and use the CHAT tool in public deliberations to prioritize nutrition interventions in rural settings with low levels of literacy. These communities prioritised both nutrition-sensitive and nutrition-specific interventions. Attending to community derived nutrition priorities may improve the relevance and effectiveness of nutrition health policy, since these priorities reflect the context in which such policy is implemented.